PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TRANSPARANSI - Dian Ramadhani; Raja Adri Satriawan Surya; Arumega Zarefar (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This study aims to examine the influence of corporate governance mechanisms to transparency. Corporate governance mechanisms examined in this study include internal mechanism consisting of: commissioners, managerial ownership, foreign ownership, debt financing, and audit quality. The population in this study is a registered company in Indonesia Stock Exchange for the period 2015 - 2018. The sample in this research determined by purposive sampling method with a total sample of 103 annual reports. Statistical tests showed that the board of directors, managerial ownership, foreign ownership, debt financing has no effect on the performance of the company while the quality of the audit have an impact on transparency.